A novel formulation design based on hetero-templated solid lipid microparticles to improve the solubility of anti-inflammatory piroxicam for oral administration. (8th February 2022) - Mumuni, Momoh A.; Amarachi, Chime S.; Victor, Anih C.; Romanus, Omeh C.; Ogbonna, Josephat; Aminu, Nafiu; James, Oyeniyi Y.; Muhammed, Achor; C. Franklin, Kenechukwu; Díaz, David Díaz
Abstract : The aim of the work was to formulate piroxicam-loaded solid lipid microparticles (SLMs) using natural biodegradable lipids and to evaluate the in vitro and in vivo properties of the formulations. Abstract : The aim of the work was to formulate piroxicam-loaded solid lipid microparticles (SLMs) using natural biodegradable lipids and to evaluate the in vitro and in vivo properties of the formulations. The lipid matrix composition consisted of 1 : 2 ratios of dika wax from Irvingia gabonensis and goat fat or beeswax. Varying amounts of the drug (0.5, 0.25 and 0.1%) were loaded into the SLMs. The SLMs were formulated using a melt homogenization method and analysed using animal model standard methods. In vivo anti-inflammatory studies were performed using Wistar rats and showed stable formulations with spherical particles within the range of 35 ± 0.577 to 50 ± 1.527 μm. The encapsulation efficiency (EE) ranged from 43.20% to 89.03% and was significantly affected by the amount of drug loaded ( p < 0.05). The formulations also exhibited a stable pH from 24 h to 2 months, meaning that there was no degradation of the active pharmaceutical ingredient (API) and the excipients. The in vitro drug release increased with the amount of drug loaded with an approximately 86% release at 600 min for formulations containing 0.5% drug, and 24% for formulations with 0.1% drug. Absorption of the SLMs was enhanced compared with a market formulation and the SLMs had better anti-inflammatory properties, which attests to the effects of the lipids at improving the oral absorption of piroxicam. Hence, piroxicam-loaded SLMs are a possible alternative to the current market formulations.